Efektivitas Penggunaan Media Pembelajaran Berbasis Edlink Sebagai Alat Evaluasi Pembelajaran Di SMP Nasional Makassar - Anti , Sri; Bahri, Aliem; Nasir (Almeera Education, 2022)
Research on the effectiveness of using Ed-link learning media as a learning evaluation tool at Makassar National Middle School aims to determine the effectiveness of using the Ed-link application as a learning evaluation tool. This type of research uses a quantitative method with a pre-experimental research design that uses one sample class in the form of pre-test and post-test. The data collection technique in this study was observation and test data analysis. The technique used was descriptive statistical analysis. The subjects in this study were students of class VII.B Makassar National Middle School in the 2022/2023 academic year, a total of 32 students. Based on data analysis, discussion of research results regarding the effectiveness of using learning media as a learning evaluation tool in Indonesian subjects, literary work entitled that: the ed-Link application is effectively used as an alternative learning evaluation tool at Makassar National Middle School with scores from observations of the use of ed- link in Indonesian subject class VII B is in a very good category which can be seen from the results of student learning through descriptive statistical analysis before using the media application ed-link, the average student score is still below the KKM after using the media, the average student score increases above KKM . It turns out that the value of the post test results, which is 2,422, is greater than the pre-test result value, which is 30.92. From the results of this study it can be interpreted that the use of ed-link as a learning evaluation tool in Indonesian subjects at the Makassar National Middle School is effective.